Numerical investigation of heat and mass transfer for unsteady multiphase flow in a vented cavity filled with hybrid nanofluid - Muhammad Ashhad Shahid; Mojtaba Dayer; Muhammad Adil Sadiq; Haris Ali; Ishak Hashim (Alexandria Engineering Journal)
Effective heat and mass transfer is crucial for enhancing efficiency and performance, particularly under varying flow conditions in devices such as heat exchangers, microfluidic systems, and chemical reactors. The current study investigates the effect of novel combination of unsteady condition and multiphase flow effect on hybrid nanofluid (HNF) convective heat and mass transfer (CHMT) within a vented cavity. The investigation employs a novel dimensionless mathematical model to explore these dynamics using Buongiorno’s approach, which considers Brownian motion and thermophoresis in nanofluids. Numerical simulations are conducted utilizing the Finite Element Method (FEM) to discretize the dimensionless governing equations. A parametric study is conducted to investigate the influence of key parameters, including the number of undulations (N) in the side walls of the cavity, Rayleigh number (Ra), and inflow velocity (Vinlet), on the Nusselt number (Nu¯) and Sherwood number (Sh¯). The analysis presents visualizations of streamlines, isothermal lines, and normalized solid volume fractions. Peak Nu¯ and Sh¯ of 4.0878 and 5.2526, respectively, indicated optimal heat and mass transfer efficiency, particularly under conditions that effectively disrupt the concentration boundary layer. The findings from this research are expected to contribute towards the development of more efficient nanofluid-based systems, particularly in systems with irregular geometries.